Is Standing for Women a Stand Against Terrorism? Exploring the Connection Between Women's Rights and Terrorism. Issue 1 (2nd January 2016) - Harris, Cameron; Milton, Daniel James
Abstract : Previous large-N studies have found that the advancement of women's rights leads to a decline in conflict, but no large-N research has explored the possibility of a similar relationship between women's rights and terrorism. Nevertheless, policymakers have long argued that the advancement of women's rights forms a key component of counterterrorism policy. Simply put, we lay out a rationale for the argument that increased women's rights reduce the likelihood of terrorism. We test this hypothesis using CIRI's women's rights data combined with two datasets accounting for domestic terrorism and the production of transnational terrorism. While the results show that women's rights overall are not a panacea for both types of terrorism, the provision of women's rights is shown to have a negative relationship with domestic terrorism. States and international institutions should take the differing effects of women's rights across different types of terrorism into account when designing counterterrorism policies.